Strategies and Methods for Memorizing al-Qur’an: A Comparative Analysis of al-Qur’an Memorization Systems at Ummu Aiman and An-Nahl Islamic Boarding Schools in Kampar, Riau - Jannah, Miftahul; Hakim, Lukmanul; Saifullah, Saifullah (Al-Qudwah, 2025)
This study aims to compare the Qur’an memorization methods employed at two specialized Tahfidz Islamic boarding schools: Ummu Aiman and An-Nahl Kampar in Riau. Both institutions implement the Wahdah method, a technique that involves memorizing one verse sequentially through repeated recitation to establish a strong and systematic memory pattern. This research adopts a qualitative approach, utilizing an in-depth field study to examine the characteristics of the memorization methods and to identify the similarities and differences in the memorization practices at both schools. The findings indicate that the Wahdah method serves as the foundational basis for memorization learning in both pesantrens. However, notable differences exist in the organization of halaqah (study circles), the habituation methods employed prior to memorization, and the establishment of memorization targets. At Ummu Aiman Islamic boarding school, students are required to attend tahsin classes to perfect their Qur’anic recitation according to proper tajwid rules before commencing the memorization process. In contrast, at An-Nahl Islamic boarding school, students are directed to begin memorizing according to predetermined tahfidz targets without first participating in recitation habituation classes. This study provides a comprehensive and informative comparative analysis of the Wahdah method as practiced in these Tahfidz pesantrens. The results can serve as a strategic reference for developing more effective and efficient Qur’an memorization teaching methods and assist similar educational institutions in designing memorization programs tailored to the needs and characteristics of their students. Abstrak: Penelitian ini bertujuan membandingkan metode menghafal Al-Qur’an yang diterapkan di dua pesantren khusus Tahfidz, yaitu Pondok Pesantren Ummu Aiman dan Pondok Pesantren An-Nahl Kampar, Riau. Kedua pesantren tersebut menggunakan metode wahdah, yaitu teknik menghafal satu ayat secara berurutan dengan pengulangan berulang untuk membentuk pola ingatan yang kuat dan sistematis. Penelitian ini menggunakan pendekatan kualitatif dengan studi lapangan mendalam yang memfokuskan pada karakteristik metode penghafalan, serta identifikasi persamaan dan perbedaan dalam pelaksanaan hafalan di kedua pesantren. Hasil penelitian menunjukkan bahwa metode wahdah menjadi landasan utama pembelajaran hafalan di kedua pesantren, tetapi terdapat perbedaan pada aspek pembagian halaqah, metode pembiasaan sebelum menghafal, serta penetapan target hafalan. Pondok Pesantren Ummu Aiman mewajibkan santri mengikuti kelas tahsin untuk memperbaiki bacaan Al-Qur’an sesuai kaidah tajwid yang benar sebelum memulai proses menghafal. Sebaliknya, Pondok Pesantren An-Nahl langsung mengarahkan santri menghafal sesuai target tahfidz yang telah ditentukan tanpa melalui kelas pembiasaan bacaan terlebih dahulu. Penelitian ini memberikan gambaran komparatif yang mendalam dan informatif mengenai praktik metode wahdah di pesantren-pesantren tahfidz tersebut. Hasilnya dapat menjadi acuan strategis dalam mengembangkan metode pembelajaran tahfidz Al-Qur’an yang lebih efektif dan efisien, serta membantu institusi pendidikan serupa dalam merancang program penghafalan yang sesuai dengan kebutuhan dan karakteristik santri.